Dry cultivation with ratoon system impacts rice quality using rice flour physicochemical traits, fatty and amino acids contents. (December 2021) - Chen, Zongkui; Li, Ping; Xiao, Junchen; Jiang, Yang; Cai, Mingli; Wang, Jinping; Li, Chengfang; Zhan, Ming; Cao, Cougui
Graphical abstract: Highlights: High-quality cultivar has higher rice quality in dry cultivation in ratoon season. The accumulation of fatty acids and amino acids assists the rice quality. Formation of amylopectin optimize crystallites traits to improve rice quality. The main or diversity of functional groups support rice quality. Abstract: A field experiment was conducted to explore the impact on rice quality using high-quality (HH) or drought-resistant (HY) cultivars under flooding irrigation (F) or dry cultivation (D) in ratooning rice system by evaluating the metabolism or physicochemical traits of starch, fatty acids, and amino acids affecting grain quality. Compared to FHY and DHY in the main or ratoon season, DHH in ratoon season (DHHR) exhibited a higher appearance and processing quality but lower cooking quality. DHHR mainly synthesized long branch chain amylopectin to construct the crystalline regions with increased crystallinity, crystallites size, interplanar spacing, dislocation density, Asp and Thr in brown and head rice. Also, it accumulated more of C16:0, C18:0, C18:1, C18:2, and C18:3 but reduced glutelin in head rice. An increase in functional groups and diversity was seen in brown and head rice, respectively. Overall, these traits improved the processing, appearance, and pasting quality of DHHR.